PENDIDIKAN EMOSIONAL DALAM PASTORAL KONSELING UNTUK REMAJA - Richi Salenda; Monica Erika Gracia Oba; Shinta Christina (PT. Giat Konseling Nusantara, 2025)
Emotional education plays a crucial role in adolescent development, especially in helping them manage emotions and build optimal emotional intelligence (EQ). This article discusses the role of emotional education in pastoral counseling for teenagers, designed to enhance their ability to face life's challenges, build healthy social relationships, and strengthen their character. Emotional intelligence includes self-management, relationship management, self-awareness, and social awareness, all of which can be trained and learned. In this context, pastoral counseling serves as an effective approach, integrating spiritual values such as love, forgiveness, and patience, while providing the community support essential for the emotional development of teenagers. Additionally, through techniques such as spiritual reflection, prayer, and Bible meditation, pastoral counseling helps teenagers overcome anxiety, control emotions, and improve the quality of interpersonal relationships. In conclusion, emotional education within pastoral counseling is an effective means of supporting the development of emotional intelligence in adolescents, using a holistic approach grounded in spiritual values.